Using a weight of evidence approach to identify sources of microbiological contamination in a shellfish-growing area with “Restricted” classification - Campos, Carlos J. A.; Kelly, Laura T.; Banks, Jonathan C. (Environmental monitoring and assessment, 2023)
Shellfish-growing areas in rural catchments are occasionally affected by elevated faecal contamination from diffuse sources and may be subject to frequent harvest closures/classification downgrades. We combined traditional risk management methods based on sanitary surveys and monitoring of Escherichia coli in seawater and shellfish with faecal source tracking, bacterial source apportionment, and hydrometeorological modelling to determine the causes of elevated E. coli concentrations contributing to harvest closures in Papanui Inlet (Aotearoa New Zealand). These multiple lines of evidence were used to inform a weight of evidence assessment of bacterial contamination in the inlet. Ruminant livestock was estimated to contribute 80% of the faecal coliform loading. Concentrations of E. coli in seawater were low (≤ 87 MPN 100 ml −1 ) whilst concentrations in tuaki/cockles/little neck clams ( Austrovenus stutchburyi ) occasionally exceeded the “Approved” classification limit (230 MPN 100 g −1 ). The most frequent positive genetic markers in seawater were the seagull ( Catellicoccus marimammalium ) (54% of seawater samples), and in shellfish, the bovine and seagull markers (both 12.5% of shellfish samples). Solar radiation was negatively correlated with E. coli in tuaki. We found that the growing area is affected by faecal inputs from animal and, to a lesser extent, human (septic tank discharges) sources which elevate contamination to levels detectable in tuaki but not in seawater, particularly in the summer months. The innovative approach can enhance the management of shellfish-growing areas affected by intermittent contamination and enables more targeted action to reduce pollution to improve shellfish water quality.